2016
DOI: 10.1002/adfm.201601123
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Reduced Graphene Oxide Nanohybrids of Chiral Functional Naphthalenediimides for Prostate Cancer Cells Bioimaging

Abstract: This study reports on the supramolecular assemblies formed between planar carbon systems (PCSs) such as thermally reduced graphene oxide (TRGO) and its small‐molecule model system coronene and a series of d‐ and l‐α amino acid derivatized naphthalenediimides (NDIs) where the halogen substituents (X = F, Cl, Br, I) are varied systematically. Confocal fluorescence microscopy of NDIs, NDI•coronene, and NDI•TRGO complexes is performed proving the uptake and stability of such complexes in the cellular environment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 78 publications
2
47
0
Order By: Relevance
“…A minor and longer second component (τ2=3216.5 ps, a2=11.8%) was also detected. As previously reported, the presence of a second longer component may suggest the presence of NP aggregates in suspension . However, the percentage of such secondary component, although significant, remains lower (11.8%) than that previously reported for nanocomposite materials (31.1%) .…”
Section: Resultsmentioning
confidence: 39%
See 1 more Smart Citation
“…A minor and longer second component (τ2=3216.5 ps, a2=11.8%) was also detected. As previously reported, the presence of a second longer component may suggest the presence of NP aggregates in suspension . However, the percentage of such secondary component, although significant, remains lower (11.8%) than that previously reported for nanocomposite materials (31.1%) .…”
Section: Resultsmentioning
confidence: 39%
“…Adapting the methods established by Wu et al . and Jacinto et al ., the fluorophores were incorporated hereby using a rapid and simple one‐step microemulsion method. TEM micrographs of such NPs are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement to the observations for the single‐photon excitation mechanism, the covalent functionalisation of SWNTs results in a more significant lifetime shortening. The appearance of a second longer minor component suggests instead the presence of unquenched species free in solid state (free‐based or zinc porphyrins) or their supramolecular self‐assembled structures …”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported that these changes in lifetime upon complexation, particularly the presence of a shorter lifetime component, may account for a photo‐induced excited‐state energy transfer occurring between the closely bound donor–acceptor aromatic chromophores and planar carbon‐based materials . Therefore, it is reasonable to conclude that a Förster resonance energy transfer (FRET) occurs in these systems, in which the porphyrins act as FRET donors and the SWNTs as the corresponding FRET acceptors …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation